No Fault Compensation for Medical Injuries - Flis, Vojko (Medicine, Law & Society, 2016)
For  decades  in  both  Europe  and  the  United  states  ,  the issue  of  compensation  for  victims  f  medical  injuries  has  led  to lively debates.  Many scholars have analyzed the adverse effects of the  „tort  system”  (based  on  negligence  standards  and  court proceedings) on the increasing costs of insurance premiums, on the patient-doctor  relationship  and  the  quality  of  care.  These  debates have  led  to  changes  in  compensation  in  some  countries. Compensation  would  be  based  not  on  negligence,  but  rather  on  a broader avoidable medical injury standard. Some nations have long operated  administrative  schemes  based  on  no  fault  principle.  No fault  compensaton  model  for  victims  of  medical  injuries  might  be characterized by the choices it makes regarding some key issues: (a) the definiton of compensation criteria in particular the status given to fault; (b) the organization of the decision -making process. What type  of  body  adjudicates  medical  claims?  (c)  Who  finances  the mechanism. What injuries are likely to be compensated for, to what extent and by whom? This article reviews the origins and operations of the no fault systems, the evolution of their compensation criteria, and how these criteria are actually applied.
Keywords: injury; compensation; liability; medical; errors; negligence